EVALUASI MUTU SOSIS ANALOG JANTUNG PISANG DAN TEMPE - ANISA MUSTIKA; AKHYAR ALI; DEWI FORTUNA AYU (Jurnal Sagu, 2018)
The purpose of this study was to obtain the best formulation of analoq sausage made from banana’s blossomand tempeh that meet the standard quality of sausage. The research used Completely Randomized Designwith five treatments and four replications. The treatments were ratio of banana’s blossom and tempeh 50:50,40:60, 30:70, 20:80, and 10:90. Data obtained were analyzed using Analysis of Variance and followed byDuncan’s New Multiple Range Test at 5% level. The results showed that ratio of banana’s blossom andtempeh in each treatment significantly affected moisture, protein, fat, and crude fiber contents. The treatmentsalso significantly affected colour and flavor, but didn’t significantly effected texture sausage. The besttreatment was a sausage which made from ratio of banana’s blossom and tempeh 10:90. The sausage hadmoisture content 48.50%, ash content 2.41%, protein content 17.11%, fat content 9.81%, carbohydratecontent 24.90%, and crude fiber content 2.20%. Panelist like the sausage in hedonic test, while in descriptivetest the sausage had yellow colour, tempeh flavor, tempeh taste, and slightly chewy texture.